An integrated model of marketing knowledge – a tacit knowledge perspective. Issue 1 (8th July 2019) - Zebal, Mostaque; Ferdous, Ahmed; Chambers, Colin
Abstract : Purpose: The purpose of this paper is to develop and propose an integrated model of marketing knowledge from a tacit knowledge management perspective. This paper further aims at developing a linkage between explicit knowledge perspective (internal and external marketing) and tacit knowledge orientation of an organization, leading to improved business success. Design/methodology/approach: This paper develops a conceptual model showing the integration of the internal, tacit and explicit knowledge perspectives that results in improved business success. The proposed model and associated propositions are drawn from the synthesis of relevant knowledge and marketing literature. Findings: Five major associated propositions are offered in the paper, which inform both scholars and practitioners about what constitutes a holistic market orientation and how organizations can achieve business success by adopting both an internal and external orientation to tacit and explicit knowledge management. Originality/value: The model makes an original contribution to theoretical and organizational marketing management knowledge. It does this by extending the conceptual and operational boundaries of existing models of internal and external marketing, aimed at helping organizations achieve competitive advantage and business success.